Adsorption of Benzoic and Salicylic Acids Using Sodium and Intercalated Bentonite in Aqueous Solution - Nadia Bensid; Yamina Berredjem; Zhour Hattab; Ridha Djellabi; Ouahida Khiereddine; FarhiHailaimia; Pierre Magri; Ahmed Boulmokh (American Scientific Publishers, 2016)
The aim of this study was to apply a local betonite (Algeria) purified and intercalated with a surfactantnamely dodecyltrimethylammonium bromide (DTMAB) as an adsorbent to remove benzoic acid (BA) and salicylic (SA) which could be present in wastewaters. This intercalation process leads to improve the porous texture of materials that allows adsorbing efficiently organic compounds. The effect of various experimental parameters was investigated using a batch adsorption technique. The equilibrium adsorption data were well described by the Freundlich and Langmuir isotherms. The adsorption kinetics of both acids could be considered as pseudo-first order with internal diffusion.The capacity of DTMA–bentonite for Benzoic acid and Salicylic acid was found to be around 5 and 3.5 times respectively higher than that of Na–bentonite at 45 C. The thermodynamic study showed that the adsorption is not spontaneous and endothermic.